STRATEGI PEMBELAJARAN INOVATIF DAN PENGALAMAN MAHASISWA DI SMK ADI LUHUR JAKARTA - Nurmawati, Nurmawati; Wulandari, Sinthya; Isliyah, Intan; Putri, Tiara Alamsyah; Fitria, Jumiati Rahmadhani; Hidayah, Amelia Putri; Ma’mur, Nia Nurhaliza; Salsabila, Zahidah; Nurjanah, Fajriyah Septi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The School Field Introduction Program (PLP) aims to provide education students with direct experience in a school environment. Conducted at SMK Adi Luhur Jakarta, this program lasted for four months and involved students from various study programs. The activities included observation, lesson plan preparation, teaching and learning processes, as well as collaboration with mentor teachers. The results demonstrated that students were able to develop pedagogical competence, understand students' needs, and enhance professionalism through practical experience. By integrating theory and practice, this program contributes to improving the quality of education and prepares students to become adaptive and competent educators.